PENGARUH STRUKTUR MODAL DAN NON PERFORMING LOAN TERHADAP NILAI PERUSAHAAN MELALUI PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Verawati, Verawati; Wiryaningtyas, Dwi Perwitasari; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
The company is an organization that has an important role in the economic development of a country. The purpose of this study was to determine the effect of capital structure and non-performing loans on company value through profitability as an intervention variable. The populations in this study are conventional commercial bank companies listed on the Indonesian Stock Exchange. The sampling technique for this study used a purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that capital structure has no significant effect on profitability, non-performing loans have no significant effect on profitability, capital structure has no significant effect on company value, non-performing loans have not proven to have a significant effect on company value, profitability has an effect significant to company value. The results of the indirect hypothesis test show that the variable capital structure has a positive but not significant effect on company value through profitability, non-performing loans have a negative effect on company value through profitability but not significant.